Application of GQM+Strategies in a Multi-industry State-Owned Company: An Experience Report - López Herrera, Gustavo (2016)
Technological applications have an increasingly important role in most companies. Investment in Information Technologies (IT) is also growing in most of them. The need to align IT-related goals with the company’s strategic goals becomes imperative. GQM+Strategies is an approach to align organizational goals, strategies, and measurements at different levels of an organization. This paper describes experiences learned from a GQM+Strategies implementation at a large multi-industry state-owned company. The implementation was conducted by an academic research team joined by representatives of the company. Results showed an improved alignment and integration of different goals. Moreover, a holistic goal visualization was achieved, even though the company works in two different industries. As a state-owned company, external pressures force continuous planning. Sometimes, inadvertently designing those plans is the only goal achieved (i.e., plans are never executed). Using GQM+Strategies, the research team leveraged the separation of goals and strategies, allowing identification of redundancies and replicated efforts across the company. The implementation of the GQM+Strategies approach in such a complex context was very valuable. However, it also required a large amount of effort from the researchers and company representatives.